Engineering Internet QoS - Jha, Sanjay (Artech House telecommunications library., 2002)
From the basics to the most advanced quality of service (QoS) concepts, this all encompassing, first-of-its-kind book offers an in-depth understanding of the latest technical issues raised by the emergence of new types, classes and qualities of Internet services. . This books provides sufficient depth for major QoS concepts and architectures. The book provides end-to-end QoS guidance for real time multimedia communications over the Internet. It offers you a multiplicity of hands-on examples and simulation script support, and shows you where and when it is preferable to use these techniques for QoS support in networks and Internet traffic with widely varying characteristics and demand profiles. This practical resource discusses key standards and protocols, including real-time transport, resource reservation, and integrated and differentiated service models, policy based management, and mobile/wireless QoS. The book features numerous examples, simulation results and graphs that illustrate important concepts, and pseudo codes are used to explain algorithms. Case studies, based on freely available Linux/FreeBSD systems, are presented to show you how to build networks supporting Quality of Service. using Linux/FreeBSD PCs. Online support material including presentation foils, lab exercises and additional exercises are available to text adaptors.